Goal setting for WHO guideline adherence: accelerometer steps/day translation of moderate-to-vigorous physical activity in older adults - Chen, I-Fan; Chen, Jiaren; Lai, Ting-Fu; Liao, Yung; Park, Jong-Hwan; Cheng, Chih-Fu (Frontiers in Public Health, 2025)
BackgroundWalking is a fundamental and accessible physical activity (PA) for older adults. Using daily step counts to self-monitor adherence to the World Health Organization’s (WHO) PA guidelines may facilitate health promotion and promote behavioral changes. This study aimed to determine the step count equivalents for achieving 30 min/day and 150 min/week of moderate-to-vigorous PA (MVPA) among older adults in Taiwan.MethodsThis cross-sectional study was conducted from May to August 2023. Community-dwelling adults aged ≥65 years were recruited through convenience sampling from local communities in northern Taiwan, with support from community leaders and activity centers. Participants were required to be capable of walking independently. Daily step counts and MVPA were measured using triaxial accelerometers. Linear regression models, including log-transformed step counts and MVPA, were used to assess equivalence.ResultsIn total, 191 older adults participated in the study (42 males, 149 females). Engaging in 30 min of MVPA daily translated to approximately 8,602 steps/day for males and 8,940 steps/day for females. Weekly MVPA of 150 min was equivalent to approximately 56,028 steps/week for males, 58,988 steps/week for females, and 57,000 steps/week overall (or 8,142 steps/day).ConclusionAmong older adults, reaching at least 8,602 steps/day is a good indicator of meeting the WHO’s recommendation of 30 min/day MVPA, whereas 57,000 steps/week corresponds to 150 min/week of MVPA. These step-based thresholds provide practical and easy-to-understand targets for self-monitoring daily activity levels and offer a behavioral foundation for PA promotion strategies aimed at improving the health of aging populations.